A Review on Research Advances and Applications of Basalt Fiber-Reinforced Polymer in the Construction Industry - Sheng-Jie Duan; Ru-Ming Feng; Xin-Yan Yuan; Liang-Tao Song; Gen-Shu Tong; Jing-Zhong Tong (Buildings)
Compared to glass fiber-reinforced polymer (GFRP) and carbon fiber-reinforced polymer (CFRP), basalt fiber-reinforced polymer (BFRP) offers distinct advantages, including the relatively lower cost and superior creep resistance. As a result, its application in the construction industry has been gaining growing attention. This paper begins by providing an overview of the fundamental background, as well as the mechanical and microscopic properties, of BFs. By exploring various application types, including one-dimensional (e.g., bars, cables), two-dimensional (e.g., grids, sheets), and three-dimensional (e.g., profiles) applications, the research progress of BFRP products in the construction industry is comprehensively summarized. Research has demonstrated the effectiveness of BFRP in a variety of structural applications, such as reinforcing existing structures (e.g., concrete or masonry) using BFRP bars, grids, or sheets, and the development of novel design concepts that integrate BFRP products with existing structural systems. Furthermore, this paper identifies unresolved challenges and proposes potential research directions, intending to promote BFRP’s broader adoption as a standardized and innovative material in the construction industry.